A RARE CAUSE OF HIGH ASTIGMATISM IN PSEUDOPHAKIA - Malik, Hajra Arshad; Khalid, Maham; Sabih, Rayyan; Khan, Hina; Asrar, Aamir (Journal of Ayub Medical College Abbottabad, 2022)
We present a case of a 65-year-old Pakistani woman who underwent an uneventful standard left phacoemulsification with posterior chamber intra-ocular lens placement for a mature senile cataract. She was observed to develop post-operative astigmatism secondary to a tilted intra-ocular lens and required repeat surgical intervention to correct the malposition. Per-operatively, the lens was found to be defective with a fixed bend at the haptic-optic junction which necessitated the need for an intra-ocular lens exchange procedure that restored adequate vision. The study highlighted defects in the structural integrity of intra-ocular lenses as an important differential to consider in such cases, and established lens replacement as a successful intervention to improve visual outcome.